Zoning policy for admission of new students: How is the implementation in Lamandau? - Ely Suntiana; Syamsuri Syamsuri; Djoko Raharjo (Psychology, Evaluation, and Technology in Educational Research, 2022)
The study aimed to find out and describe the implementation of Permendikbud No 1 of 2021 which regulates the zoning system in admission of new students in 3 schools in Bulik district, Lamandau regency. At the Junior High School level, a zoning system is applied to 3 schools in Lamandau Regency, Central Kalimantan Province. The method used qualitative data with interviews, documentation, observation, and data triangulation for data collection techniques. The study used the Theory of Implementation of George Edward III and Van Meter and Van Horn with variables of Resources, Communication, Bureaucratic Structure, Disposition, characteristics of implementing agents, Standards and policy objectives, and Conditions of the social, political and economic environment. It concluded that the implementation of Permendikbud No 1 of 2021 was well-implemented by the support of the local government, related agencies, and schools. Dissemination Information has been conveyed, by both the government and schools through many ways, such as official-social media, letters, banners, pamphlets, school websites to groups with parents (Whats Apps). The problem arise is that communication has not been carried out thoroughly and effectively so that there are parents and prospective students who do not understand and confused about the zonation system.